The Relationship Between Islamic Religious Education Learning Outcomes and Student Personality at SMP Negeri 03 Pagar Alam - Rahman; Murlita; Nova Tri Evriani; Nurlis; Hermi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The aim of this research is to determine the relationship between students' PAI (Islamic Religious Education) learning outcomes and their personality, as well as to identify the factors that hinder students' personality development. This research is a descriptive quantitative study. The data collection methods used in this study were observation, questionnaires, and documentation. The collected data were inductively presented in numerical form. The sample used in this study was purposive sampling, consisting of 27 students. The data analysis techniques included validity tests, reliability tests, normality tests, homogeneity tests, linearity tests, and hypothesis testing. The results showed that in the hypothesis test, the researcher used the rule of comparing the t-calculated value with the t-table value. Based on the t-values: the t-calculated value was 6.347 > the t-table value of 2.042 (t-table 5%, n=27). This indicates a positive relationship between PAI learning outcomes and students' personality in SMP Negeri 3 Kota Pagar Alam. Thus, it can be concluded that Ha is accepted and Ho is rejected. The factors affecting students' personality are 1) genetic factors, 2) environmental factors, and 3) school factors.